Modified Single Stage AC-AC Converter - Derick Mathew; Athira P Ashok; Bincy M Mathew (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The paper describes the single stage AC-AC converter. This converter is a good alternative to quasi direct back to back converter. This single stage converter is called Matrix Converter. Matrix converter is an array of controlled semiconductor switches that connects three phase source to the three phase load. This converter provides bidirectional power flow, sinusoidal input and output waveforms and they have no dc link storage elements. Simulation model and results presented showing Venturini control method of matrix converter.